Study of Algorithms and Techniques of Web Search Engines Indexing (International Journal of Scientific Research in Science and Technology, 2025)
In this paper, we compressing the huge index of a Web Search Engine (WSE) entails a better utilization of memory hierarchies and thus a lower query processing time. During the last years several works addressed the problem of index compression. The majority of them focused on devising effective and efficient methods to encode the document identifiers (DocIDs) contained in the posting lists of Inverted File (IF) indexes[1-5]. Since posting lists are ordered sequences of integer DocID values, and are usually accessed by scanning them from the beginning, these lists are stored as sequences of d-gaps, i.e. differences between successive DocID values.